2008
DOI: 10.1007/s00442-008-1097-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stream predator richness on the prey community and ecosystem attributes

Abstract: It is important to understand the role that different predators can have to be able to predict how changes in the predator assemblage may affect the prey community and ecosystem attributes. We tested the effects of different stream predators on macroinvertebrates and ecosystem attributes, in terms of benthic algal biomass and accumulation of detritus, in artificial stream channels. Predator richness was manipulated from zero to three predators, using two fish and one crayfish species, while density was kept eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 73 publications
2
22
1
Order By: Relevance
“…At the individual host species level, parasite biodiversity has traditionally been studied in relation to host body size (Price and Clancy 1983), geographical range (Dritschilo et al 1975), population density (Morand et al 2000), latitudinal distribution (Poulin 2001), and diet (Bell and Burt 1991) using interspecific comparisons among host species. This finding corroborates the widespread correlation of biodiversity between resource and consumer levels in free-living communities (Siemann et al 1998, Biesmeijer et al 2006, Nilsson et al 2008. The present analysis is the first to provide meta-analytical insights into the patterns of parasite biodiversity at the broader community level.…”
Section: Discussionsupporting
confidence: 86%
“…At the individual host species level, parasite biodiversity has traditionally been studied in relation to host body size (Price and Clancy 1983), geographical range (Dritschilo et al 1975), population density (Morand et al 2000), latitudinal distribution (Poulin 2001), and diet (Bell and Burt 1991) using interspecific comparisons among host species. This finding corroborates the widespread correlation of biodiversity between resource and consumer levels in free-living communities (Siemann et al 1998, Biesmeijer et al 2006, Nilsson et al 2008. The present analysis is the first to provide meta-analytical insights into the patterns of parasite biodiversity at the broader community level.…”
Section: Discussionsupporting
confidence: 86%
“…Experimentation in artificial stream channels that emulate natural streams examined the effects of these predators, individually and in combination, on their major invertebrate prey and on algal production. The study revealed that predators enhanced algal production (Nilsson et al 2008). Moreover, the combined predator effect was the average of the individual predator effects and was brought about largely by nonconsumptive rather than consumptive predator effects.…”
Section: Discussionmentioning
confidence: 93%
“…But, averaging effects seem to play out in a system with greater intermediate species diversity in which predator hunting mode and habitat domain are also known. In streams of northern Europe, two predatory fish, stone loach (Barbatula barbatula) and brown trout (Salmo trutta) have identical hunting modes (active) but they have complementary habitat domains where the loach resides near the benthic zone and the trout resides in the water column (Nilsson et al 2008). Experimentation in artificial stream channels that emulate natural streams examined the effects of these predators, individually and in combination, on their major invertebrate prey and on algal production.…”
Section: Discussionmentioning
confidence: 99%
“…Over the 5 week period of study, we observed a large reduction in the abundance of shredders. Although it is acknowledged that the use of mesocosms may lead to overestimation of predation rates due to more homogenous habitat than in the wild (Nilsson et al, 2008), the changes observed, even if at lower magnitude, are likely to have longer term cascading effects on the community. The predatory impact on shredders may lead to a change in the processing of basal resources, with implications for nutrient cycling and therefore availability to primary producers (Vanni, 2002).…”
Section: Discussionmentioning
confidence: 99%